Occupational Stress and Burnout among Staffs in Hospitals: A Systematic Review - Sayapathi, Balachandar S.; Denis, Nastassia; Su Ting, Anselm (Journal of History Culture and Art Research, 2020)
Occupational stress and burnout among staff were appraised by carrying out a systematic review. There has been an increased prevalence of work-related stress and burnout worldwide. This occupational disorder brings a total of 19-30% among common working population. The increased prevalence of burnout was seen predominantly among the staff of healthcare. Around 25-75% of burnout was noted particularly among the physicians. Around 10% of occupational diseases constituted burnout. The stress levels are measured among the staff of different groups to battle stress and burnout by executing appropriate strategies and hence, their performances are improved to attain the anticipated results. The search was carried out from 3 major databases, i.e., PubMed, EBSCOhost: Academic Search Complete and ProQuest: Education Database for studies issued from 1st January 2007 until 1st December 2017 without language limits, but omitted dissertation and thesis, newspapers and magazines. Different research designs were comprised in this review. The studies were recognized and regained by two separate authors. There were eight papers that satisfied the necessities of this systematic review from 812 titles scanned initially. The healthcare workers in the hospital displayed mild stress in most of the studies. The main sources of stress among the staff were heavy workload and resource scarcity. Continuous stress exposure at workplace can cause burnout among healthcare workers. Stress and subsequently burnout may lead to various diseases. To alleviate their burnout effectively, the top management should focus on resources needed and to conduct regular assessment among the staff for burnout.